Design and Analysis of the Prototype of Pico Hydro Scale Submersible Type Turbine-Generator for Flat Flow River Application - Subekti, Ridwan Arief; Susatyo, Anjar; Irasari, Pudji (Teknologi Indonesia, 2012)
This paper discusses the design and analysis of prototype of submersible type turbine-generator for fl at fl ow river application. 500 W pico hydro turbine with the net head of 1 m was used. The type of turbine used was ofPropeller type with the blade profi le shape of airfoil NACA 6412 and the runner blade number of 6 pieces. Turbine and generator was aligned on one shaft (direct coupled) so that the construction was simple. The generator usedwas of permanent magnet generator type of 500 W, 500 rpm, 1 phase, 50Hz, 220 V. The turbine-generator unit was then tested in one of Kebun Raya Cibodas channels. The test was conducted at varied heads and constant loadscomprised of 5 x 100 W lights. The test results presented in the form of head vs. speed and head vs. power graphs show that the system could only have effi ciency of 19.98%.